1971
DOI: 10.1139/z71-099
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between food, phylogeny, and cellulose digestion in the Bivalvia

Abstract: The distribution of cellulase in the class Bivalvia is studied with respect to phylogenetic position, feeding category, and food. Cellulase activity in nine species is measured turbidimetrically using reprecipitated cellulase substrate, colorimetrically using methyl cellulose substrate, and histochemically with methyl cellulose film. Cellulolytic activity in these animals generally corresponds to the level of cellulose in the food. Those animals feeding on particles with a high cellulose content have high cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

1974
1974
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 0 publications
1
13
0
1
Order By: Relevance
“…Probably cellulase activity is due to the presence of micro-organisms in the gut (Stickney & Shumway, 1974;Crosby and Reid, 1971). Mattheis (1964) determined several clones of bacteria in the alimentary tracts of carp amongst which real water bacteria like Pseudomonadaceae were the predominant forms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Probably cellulase activity is due to the presence of micro-organisms in the gut (Stickney & Shumway, 1974;Crosby and Reid, 1971). Mattheis (1964) determined several clones of bacteria in the alimentary tracts of carp amongst which real water bacteria like Pseudomonadaceae were the predominant forms.…”
Section: Discussionmentioning
confidence: 99%
“…Whether cellulase activity is characteristic of the genus or is a function of the cellulose content in the food is not yet clear. Crosby & Reid (1971) claim that cellulolytic activity in bivalves corresponds to the level of cellulose in food. Similarly, Meyers & Reynolds (1957) found that cellulolytic activity of fungus on cellulose powder depends on the form of cellulose in the culture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most invertebrate phyla include members which demonstrate cellulase production, whereas vertebrates seemed to lack the capability of producing this enzyme (Yokoe & Yasumasu, 1964). Crosby & Reid (1971) in a study of bivalve molluscs, concluded that cellulase activity in these animals was a function of cellulose abundance in the food and not necessarily phylogenetically related. The studies outlined in this paper were designed to determine the incidence of occurrence of cellulase activity in the stomachs of common species of southeastern United States marine and estuarine teleost and elasmobranch fishes, and to determine if the presence or absence of cellulase activity could be related to general food habits of the fish examined.…”
Section: R Introductionmentioning
confidence: 99%
“…Atividade de β-1,4-glucanase também foi verificada para Teredo navalis Linnaeus, 1758 (Deschamps, 1957;Kadota, 1959), Bankia setacea (Tyron, 1863) (Crosby & Reid, 1971), Bankia indica [que é de acordo com Turner, 1966 Bankia Carinata (Gray) 1827] (Nair, 1955(Nair, , 1956(Nair, , 1957 e Teredo sp. (Greenfield & Lane, 1953;Greenfield, 1955).…”
Section: -Aspectos Biológicos Dos Teredinídeosunclassified